Have I ever told you black lives matter? - King, Shani M. (Tilbury House Publishers, 2021)
Celebrates the Black Lives Matter movement and offers word art and illustrations of quotes and famous Black figures from throughout history who fought for Black liberation and equality. Includes short columns profiling a wide range of notable Black men and women in history, from Sojourner Truth to Jimi Hendrix.